Finding Critical Nuclei in Phase Transformations by Shrinking Dimer Dynamics and Its Variants (Communications in Computational Physics, 2014)
We investigate the critical nuclei morphology in phase transformation bycombining two effective ingredients, with the first being the phase field modeling ofthe relevant energetics which has been a popular approach for phase transitions andthe second being shrinking dimer dynamics and its variants for computing saddlepoints and transition states. In particular, the newly formulated generalized shrinkingdimer dynamics is proposed by adopting the Cahn-Hilliard dynamics for the generalized gradient system. As illustrations, a couple of typical cases are considered, including a generic system modeling heterogeneous nucleation and a specific materialsystem modeling the precipitate nucleation in FeCr alloys. While the standard shrinking dimer dynamics can be applied to study the non-conserved case of generic heterogeneous nucleation directly, the generalized shrinking dimer dynamics is efficient tocompute precipitate nucleation in FeCr alloys due to the conservation of concentration.Numerical simulations are provided to demonstrate both the complex morphology associated with nucleation events and the effectiveness of generalized shrinking dimerdynamics based on phase field models.